2010
DOI: 10.1177/0829573509357550
|View full text |Cite
|
Sign up to set email alerts
|

Do School Bullying and Student—Teacher Relationships Matter for Academic Achievement? A Multilevel Analysis

Abstract: In extending our understanding of how the social climate of schools can affect academic outcomes, this study examined the relationship between school bullying, student— teacher (S-T) connectedness, and academic performance. Using data collected in Canada as part of a larger international study conducted by the Organisation for Economic Co-operation and Development, participants included 27,217 students aged 15 years and 1,087 school principals. Results of multilevel analyses revealed that math achievement was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
115
2
19

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(149 citation statements)
references
References 37 publications
13
115
2
19
Order By: Relevance
“…They added that students who are often subject to be bullied by their peers during school period have less engagement at school and poor grades. Konishi et al (2010) confirmed that interpersonal relationships within school environment influence academic achievement. Roman and Murillo (2011) found that aggression in schools has a negative effect on academic achievement in Latin America.…”
Section: Review Of Related Literaturesupporting
confidence: 60%
See 1 more Smart Citation
“…They added that students who are often subject to be bullied by their peers during school period have less engagement at school and poor grades. Konishi et al (2010) confirmed that interpersonal relationships within school environment influence academic achievement. Roman and Murillo (2011) found that aggression in schools has a negative effect on academic achievement in Latin America.…”
Section: Review Of Related Literaturesupporting
confidence: 60%
“…Marcela and Javier (2011) found that bullying is a serious problem throughout Latin America they indicated that; students who suffer from their peers aggression have lower performance in reading and math than those who do not; and students who are in classrooms with more physical or verbal violence perform are more worse than those in less violent classroom settings. Konishi et al (2010) found that school bullying affects negatively academic achievement. Chaux et al (2009) argued that ten to fifteen percent of adolescents worldwide are bullied two or more times a month.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…This concern especially appeared to stem from the negative influences of bullying on students' well-being. In the literature, it was well-documented that bullying had deleterious influences on students' health and led to some emotional, behavioral, social, and academic problems, such as posttraumatic stress (Mynard, Joseph, & Alexandera, 2000), depression (Çetinkaya, Nur, Ayvaz, Özdemir, & Kavakcı, 2009;Sabuncuoğlu et al, 2006), hopelessness, loneliness, suicidal ideation (Fleming & Jacobsen, 2009), problem behaviors, less social competence (Haynie et al, 2001), and lower academic achievement (Konishi, Hymel, Zumbo, & Li, 2010). Moreover, higher prevalence of bullying in school settings seemed to be another concerning issue.…”
Section: Introductionmentioning
confidence: 99%
“…A literatura tem mostrado a importância de fatores como capital social (BONAMINO et al, 2010;GOODMAN;GREGG;WASHBROOK, 2011), capital cultural (BONAMINO et al, 2010MARTELETO;ANDRADE, 2013), atitudes e comportamentos dos alunos e pais (GABLE; WOLF, 1993;GOODMAN;GREGG;WASHBROOK, 2011;LEE, 2013), interações entre alunos e professores e clima escolar (STEWART, 2008;KONISHI et al, 2010) Portanto, a partir deste estudo, verificou-se que, além de uma avaliação e definição clara dos construtos que se pretende medir, é necessária uma revisão na construção das questões dos questionários, pois várias não atendem às orientações para construção de instrumentos de medidas (PERES-DOS-SANTOS; HOGAN, 2006;PASQUALI, 1999;CLARK;WATSON, 1995). Deve-se investir tempo na padronização das escalas das respostas, na construção de orientação para os pesquisadores quanto à possibilidade de utilização das variáveis como ordinais ou intervalares e na revisão das perguntas constantes nos questionários, de modo a torná-las mais simples e claras.…”
Section: Instrumentosunclassified